Early multidisciplinary assessment was associated with longer periods of sick leave: A randomized controlled trial in a primary health care centre. (September 2013) - Carlsson, Lars; Englund, Lars; Hallqvist, Johan; Wallman, Thorne
Abstract Objective. To study the effects on sick leave from an early multidisciplinary assessment at a primary health care centre. Design. Randomized controlled trial. Setting. Patients who saw GPs at a primary health care centre in mid-Sweden and asked for a sickness certificate for psychiatric or musculoskeletal diagnoses were invited to participate. Patients included were sick-listed for less than four weeks; 33 patients were randomized either to an assessment within a week by a physiotherapist, a psychotherapist, and an occupational therapist or to "standard care". The therapists used methods and tools they normally use in their clinical work. Main outcome measure. Proportion of patients still sick-listed three months after randomization, total and net days on sick leave, and proportion who were on part-time sick leave. Results. At follow-up after three months, in contrast to the pre-trial hypothesis, there was a trend toward a higher proportion of patients still sick-listed in the intervention group (7/18) as compared with the control group (3/15). The intervention group also had significantly longer sick-listing periods (mean 58 days) than the control group (mean 36 days) (p = 0.038). The proportion of patients who were part time sick-listed was significantly higher in the intervention group (10/18) than in the control group (2/15) (p = 0.027). Conclusions. In this study an early multidisciplinary assessment was associated with longer periods on sick leave and more individuals on part-time sick leave.